The danger of the spread dangerous quarantine weed — giant ragweed (Ambrosia trifida L.) - Marieva, O.; Zhuiboroda, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The expansion of trade and economic relations with other countries increased the risk of importing new invasive types of weeds into the state. One of them is a serious danger weed — giant ragweed (Ambrosia trifida L.). This weed with high speed and aggressiveness inhabits and displacing native species in agricultural and non-arable land, including landscapes of big cities. A. trifida extends to non-arable lands with disturbed natural vegetation. This species is spreading through the contamination of seeds and agricultural equipment. It damaged soybeans, legumes and corn, as well as other grain crops. Increasing of this weed pollen in the air is a source of a massive disease with allergies. At present, there is danger of entry by this weed to Ukraine from neighboring countries.